The last girls : a novel - Smith, Lee. (North Carolina : Algonquin Books of Chapel Hill, 2002)
Thirty-five years after a trip down the Mississippi on a raft with their classmates, four women are reunited to cruise the river once again where they plan to release the ashes of a fellow rafter, Margaret "Baby" Ballou.
Keywords: CLASS REUNION